Improving Access to Integrated Behavioral Health in a Nurse-Led Federally Qualified Health Center. (May 2023) - Stalder, Sarah; Techau, Aimee; Hamilton, Jenny; Caballero, Carlo; Weber, Mary; Roberts, Mia; Barton, Amy J.
INTRODUCTION: All patients of a nurse-led federally qualified health center and faculty practice interested in medication management were automatically referred to the psychiatric mental health nurse practitioner in the clinic. This approach was not sustainable to provide access to patients who needed both simple and complex medication management. Thus, a search for a new care model that also focused on the full-scope practice of a psychiatric RN was initiated. AIMS: The specific aims of this project were to create a fully integrated, nurse-led model of a psychiatric nurse practitioner and behavioral health care team within primary care to facilitate (1) patients receiving an appropriate level of care and (2) care team members performing at the top of their scope of practice. METHODS: The guiding model for process implementation was Rapid Cycle Quality Improvement. Three task forces were established to develop interventions in the areas of Roles and Responsibilities, Training and Implementation, and the electronic health record. RESULTS: The process measures of referrals to the psychiatric care team and psychiatric assessment intakes performed as expected. Both measures were higher at the onset of the project and lower 1 year later. The outcome indicator, number of case reviews, increased dramatically over time. CONCLUSIONS: For psychiatric nurse practitioners, this quality improvement effort provides evidence that a consultative role can be effective in supporting primary care providers. Through providing education, establishing patient tiers, and establishing an effective workflow, more patients may have access to psychiatric services.